(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the social problems encountered in families raising a child with a speech impediment and their impact on the child’s development. The study highlights the impact of the psychological environment in the family, the pedagogical literacy of parents, the level of social support, and economic factors on the upbringing and social adaptation of a child with a speech impediment.